The Age-Related Association of Movement in Irish Adolescent Youth - Diarmuid Lester; Bronagh McGrane; Sarahjane Belton; Michael J. Duncan; Fiona C. Chambers; Wesley O'Brien (MDPI AG, 2017)
(1) Background: Research has shown that post-primary Irish youth are insufficiently active and fail to reach a level of proficiency across basic movement skills. The purpose of the current research was to gather cross-sectional baseline data on Irish adolescent youth, specifically the prevalence of movement skills and patterns, in order to generate an overall perspective of movement within the first three years (Junior Certificate level) of post-primary education. (2) Methods: Data were collected on adolescents (N = 181; mean age: 14.42 ± 0.98 years), attending two, mixed-gender schools. Data collection included 10 fundamental movement skills (FMS) and the seven tests within the Functional Movement Screen (FMS™). The data set was analysed using the Statistical Package for Social Sciences (SPSS) version 20.0 for Windows. (3) Results: Overall, levels of actual mastery within fundamental and functional movement were low. There were statistically significant age-related differences observed, with a progressive decline as age increased in both the object control (p = 0.002) FMS sub-domain, and the in-line lunge (p = 0.048) test of the FMS™. (4) Conclusion: In summary, we found emerging evidence that school year group is significantly associated with mastery of movement skills and patterns. Results from the current study suggest that developing a specifically tailored movement-oriented intervention would be a strategic step towards improving the low levels of adolescent fundamental and functional movement proficiency.